Effect of GnRH on reproductive activity of postpartum cow - DEEN, AMINU; KHAN, S K; GALHOTRA, M M; KHURANA, N K (The Indian Journal of Animal Sciences, 2013)
Postpartum crossbred cows (96) were subjected to an intramuscular injection of GuRH analogue, buserelin (20 ug) or saline at 2 different postpartum stages of 15-20 or 30-35 days. This induced varying degrees of synchronous FSH and LH surges. The gonadotrophic response was higher in 30-35 days postpartum group as compared to 15-20 days. Progesterone rise was observed in 3 out of 12 cows of 15-20 days group and none Out of 6 cows of 30-35 days group. The reproductive efficiency did not improve in the treated cows over the control. Despite, its stimulatory action on gonadotrophin release GnRH treatment did not induce ovarian activity in majority of the treated animals. It is concluded that GnRH could induce ovarian activity only when a respomive follicle is present in the ovary.